2019
DOI: 10.1016/j.jpag.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Self-Reported Physical Activity in a Cohort of Racially Diverse Pregnant Adolescents

Abstract: PA is low across gestation and pregnant teens spent more than half of their monitored time in sedentary activities. Targeted interventions are needed to achieve current PA goals in this pediatric obstetric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…However Gebregziabher et al [17] found that those who were less than 19 years of age were four times more likely to be physically inactive (aOR 4.7, 95% CI 1.4, 15.3) compared with those who were in 25-29-year age group. A study by Steinl et al [32] among pregnant teenagers also noted a positive correlation between age and physical activity levels. However, this current study did not include teenage pregnancies because they are considered to be high risk.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However Gebregziabher et al [17] found that those who were less than 19 years of age were four times more likely to be physically inactive (aOR 4.7, 95% CI 1.4, 15.3) compared with those who were in 25-29-year age group. A study by Steinl et al [32] among pregnant teenagers also noted a positive correlation between age and physical activity levels. However, this current study did not include teenage pregnancies because they are considered to be high risk.…”
Section: Discussionmentioning
confidence: 86%
“…Individual factors that have commonly been associated with physical activity in pregnancy are parity or number of living children, education level, employment status and body mass index (BMI); maternal age, ethnicity and history of miscarriage have been considered less frequently [15,17,19,20,[28][29][30][31][32][33]. Three studies have found that primiparity is significantly associated with physical inactivity [17,19,30], while three other studies have found that multiparity is significantly associated with physical inactivity [15,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…This state of dependence opens an avenue for low self-esteem, hopelessness, and helplessness. Additionally, it takes a psychological toll creating insecurity, depression, and anxiety (23). In families afflicted with a history of poverty, a teenage pregnancy can be devastating by reducing independence when access to adequate resources and child care assistance is already severely limited (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some young women do improve their diet in pregnancy (Soltani, Duxbury, Rundle & Marvin-Dowle, 2017), others have cited barriers to healthy eating, including a lack of money and access to food (Whisner, Bruening, & O'Brien, 2016). Although the issue of physical inactivity is not only contained to young women, studies confirm that both pregnant (Steinl et al, 2018) and postpartum young women (Behrens, Bradley, Kirby & Nanney, 2012) are insufficiently physically active. Indeed, teenage girls are consistently identified as a group that is not doing enough physical activity to meet recommendations for health (Women in Sport, 2016).…”
Section: Introductionmentioning
confidence: 99%